Thermohydraulic performance enhancement using novel hybrid corrugation configuration channels in thermal systems. (May 2022) - Kumar, Krishan; Kumar, Rajan; Bharj, Rabinder Singh
Abstract: High heat generation in the electronic components results in dire performance if it is not dissipated efficiently. The dissipation of heat from these components can be made efficient by adopting corrugated channels in the heat sink. The present work uses novel designs of the corrugation configurations to enhance the heat transfer rate. The considered corrugation configurations with three different shapes arc, trapezoidal, and triangular are inward-only (no outward configuration), non-hybrid (inward and outward configurations are same), and hybrid (inward and outward configurations are different). Numerical simulations are performed to analyze entropy generation, heat transfer, and fluid flow in the corrugated channels. Different uniform inlet velocities corresponding to Reynold numbers 15, 000, 22, 500, 30, 000, and 37, 500 are considered. All the corrugation configuration channels help in improving convective heat transfer as compared to the simple channel. The Nu is highest in the case of inward arc-outward triangular hybrid corrugation configuration at the highest considered Re . But at the same time, inward trapezoidal-outward triangular hybrid corrugation configuration channel results in the highest increment in the Nu as compared to the simple channel at the lowest Re and this increment is 68.46%. When all these channels are analyzed for the friction factor, inward trapezoidal-outward trapezoidal corrugation configurations result in the highest friction factor at all the flow rates. In terms of entropy generation assessment, the simple channel has the highest S gen while the inward arc-outward triangular hybrid corrugation configuration has the least S gen among the considered cases. The inward trapezoidal-outward triangular hybrid configuration is recommended at low Re over other configurations based on lowest N s, a equals to 0.594. Highlights: The configurations having inward-only, inward-outward non-hybrid, and inward-outward hybrid corrugations are used. Novel hybrid configurations with different inward and outward corrugation shapes are used on the corrugated wall. Nusselt number, friction factor, and entropy generation are analyzed in the channels at various Reynold numbers. Heat transfer enhancement using corrugated channels is higher as compared to simple channel at the low Reynold numbers. The hybrid configurations have better overall performance in terms of total entropy generation.